2018
DOI: 10.1016/j.bpj.2017.11.835
|View full text |Cite
|
Sign up to set email alerts
|

Lipids and Ions Traverse the Membrane by the Same Physical Pathway in the nhTMEM16 Scramblase

Abstract: From bacteria to mammals, different phospholipid species are segregated between the inner and outer leaflets of the plasma membrane by ATP-dependent lipid transporters. Disruption of this asymmetry by ATP-independent phospholipid scrambling is important in cellular signaling, but its mechanism remains incompletely understood. Using MD simulations coupled with experimental assays, we show that the surface hydrophilic transmembrane cavity exposed to the lipid bilayer on the fungal scramblase nhTMEM16 serves as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 58 publications
(94 reference statements)
9
29
0
Order By: Relevance
“…We envisage that out-of-the-groove lipid transport is enabled by groove-dependent local distortions and thinning of the membrane in the vicinity of the protein. This hypothesis is consistent with the finding that the nhTMEM16 scramblase induces a pronounced membrane thinning in the proximity of the groove in molecular dynamics calculations (18,33). An alternative interpretation of these results is that the groove could dilate to accommodate these very large headgroups, which would require a major rearrangement induced by the permeating PEGylated lipids.…”
Section: Generation Characterization and Reconstitution Properties supporting
confidence: 88%
See 2 more Smart Citations
“…We envisage that out-of-the-groove lipid transport is enabled by groove-dependent local distortions and thinning of the membrane in the vicinity of the protein. This hypothesis is consistent with the finding that the nhTMEM16 scramblase induces a pronounced membrane thinning in the proximity of the groove in molecular dynamics calculations (18,33). An alternative interpretation of these results is that the groove could dilate to accommodate these very large headgroups, which would require a major rearrangement induced by the permeating PEGylated lipids.…”
Section: Generation Characterization and Reconstitution Properties supporting
confidence: 88%
“…The cryoelectron microscopy structures of the TMEM16A channel homolog revealed that Ca 2+ gating involves the movement of the intracellular portion of the pore-lining TM6 helix (37,38). We and others identified a network of polar residues located at the extracellular entryway of the nhTMEM16 groove that is important for lipid recruitment (18,33,39) and that undergoes a conformational rearrangement to allow the groove to open, enabling penetration of the lipid headgroups and scrambling (39). We reasoned that if all lipids permeate through the groove, then impairing either conformational change should affect their scrambling rates to the same extent.…”
Section: Generation Characterization and Reconstitution Properties mentioning
confidence: 80%
See 1 more Smart Citation
“…We therefore suggest that phospholipids and Cl − ions share the same intramolecular pathway, as reported recently for nhTMEM16 by Jiang et al . (). Taken together, the present data suggest regulation of TMEM16A/ANO1 and TMEM16F/ANO6 being more complex than thought initially.…”
Section: Discussionmentioning
confidence: 97%
“…1, right protomer). Indeed, molecular dynamic simulations on TMEM16 and opsin scramblases suggest that these proteins bend and thin the membrane at the protein-lipid interface (8,13,17,23).…”
mentioning
confidence: 99%